Ascites in Dogs: A Comprehensive Study on Diagnosis and Therapeutic Management - Baria, Vinay R; Vagh, Arshi A; Bilwal, Avinash K; Damor, Jayendra R; Sherasiya, Raisudin M; Patel, Priyanshi V (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The dogs (n=29) presented at Veterinary Clinical Complex, Kamdhenu University, Junagadh with complain of abdominal distention were screened for ascites. For the diagnosis, detailed history and clinical examinations were performed together with haemato-biochmeical analysis, ascitic fluid analysis and ultrasonography, and a suitable therapeutic protocol was used. Among the confirmed cases of ascites higher incidence was found in female dogs with Labrador retriever being most affected breed and age group of 4 to 8 years most affected. Dogs with ascites displayed notable haematological alterations; including significant decrease in TEC, PCV and lymphocyte levels, while significant increase in TLC. Dogs with ascites exhibited a significant elevation in ALT, ALP, creatinine and BUN levels. Additionally, highly significant reduction was observed in total protein, albumin, and A/G ratio. The ascitic fluid’s SAAG (serum ascitic albumin gradient) values played a crucial role in determining the underlying cause of ascites. Ultrasonography emerged as a valuable imaging modality due to its ability to detect even small amount of ascitic fluid and identify accompanying alterations in echotexture of vital organs. The therapy of silymarin and supportive care proved effective in managing ascites caused by hepatic disorders. Additionally, the use of herbal nephroprotectives showed promising results in the recovery of ascites associated with renal disorders.